2020
DOI: 10.5114/ps/116968
|View full text |Cite
|
Sign up to set email alerts
|

Influence of anterior teeth inclination on the strength of incisors with post and cores

Abstract: Wprowadzenie. Zęby wychylone doprzedsionkowo stanowią problem estetyczny i biomechaniczny. Czy odbudowa protetyczna zniszczonego zęba siecznego, którego korzeń jest wychylony dowargowo sprosta siłom żucia? Cel pracy. Celem pracy była ocena wpływu wychylenia osi zębów przednich na wytrzymałość siekaczy odbudowanych wkładami koronowo-korzeniowymi. Materiał i metody. Badanie przeprowadzono metodą elementów skończonych z użyciem elementów kontaktowych. Stworzono modele 3-D zęba siecznego przyśrodkowego szczęki: mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The tissues material data and the construction material were entered in the FEM software (Table 1). 6,7 All procedures performed in studies involving human participants were in accordance with the Declaration of Helsinki of 1964. The experiment was approved by the Jagiellonian University Bioethics Committee (No.…”
Section: Methodsmentioning
confidence: 99%
“…The tissues material data and the construction material were entered in the FEM software (Table 1). 6,7 All procedures performed in studies involving human participants were in accordance with the Declaration of Helsinki of 1964. The experiment was approved by the Jagiellonian University Bioethics Committee (No.…”
Section: Methodsmentioning
confidence: 99%
“…Designing a targeted and reasonable restoration plan can minimize iatrogenic tooth fractures and significantly improve the service life of the affected teeth after restoration. Dejak et al [19] found that the force on the anterior teeth with palatal/lingual inclination was the smallest, and the greater the labial inclination angle of the anterior teeth, the greater the force. The force on the labial inclination anterior teeth repaired with post core significantly increased compared to the labial inclination anterior teeth at the same position.…”
Section: Research On the Application Of 3d Finite Element Analysis In...mentioning
confidence: 99%